Comparative Analysis of Anthropometric Parameters as Obesity Indicators for 7-8 Years-old Children of Different Resident Status - Milena Mitrovic; Katarina Dragutinovic (Journal of Anthropology of Sport and Physical Education, 2020)
The purpose of this study was determine obesity of 7-8 years-old children in the urban (Podgorica) and rural area (Zupa) of Montenegro and determine whether there is a statistically significant difference in obesity among them. The sample of respondents consisted of 85 children 7-8 years-old from Podgorica (urban) and Zupa Niksic (rural) divided into 4 sub-samples according to the criterium of gender and place of residence. Each respondent was calculated BMI and WHR, which were shown numerically and percentally, and the differences were determined using the t-test for small independent samples. The results of the study showed that there are statistically significant differences in overweight and obesity among children of both genders from Podgorica (urban) and Zupa (rural), where the children from Podgorica had significantly higher percentage of children from Zupa. We concluded that childrens from rural area are less obese than children in urban area. The reason for this should be found in the fact that childrens in rural area are more physically activity and healthier foods, which are the main reason for preventing obesity.